Profile of Serogroup Y Meningococcal Infections in Canada: Implications for Vaccine Selection - Nicole Le Saux; Julie A Bettinger; Susan Wootton; Scott A Halperin; Wendy Vaudry; David W Scheifele; Raymond Tsang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Canada is a leader in establishing routine infant immunization programs against meningococcal C disease. Currently, all provinces have routine programs to provide meningococcal C conjugate vaccines to infants and children. The result of the existing programs has been a decrease in serogroup C incidence. The second most common vaccine-preventable serogroup in Canada is serogroup Y, the incidence of which has been stable. The availability of a quadrivalent conjugate vaccine against serogroups A, C, Y and W135 focuses attention on serogroup Y disease as it becomes relatively more prominent as a cause of vaccine-preventable invasive meningococcal disease. This vaccine was licensed in November 2006 but is not routinely used except in Nunavut, New Brunswick and Prince Edward Island. To allow a better understanding of the ‘value added’ by a serogroup Y-containing vaccine, it is necessary to have a contemporary profile of Y disease in Canada. In the present paper, recent surveillance data on invasive meningococcal disease across Canada are summarized.